Main Characteristics Of The Demographic Situation And Economic And Social Development Of Kashkadarya Region - Murodova D.S (Genius Journals, 2023)
The article is devoted to the analysis of the socio-economic development of one of the leading regions of the Republic of Uzbekistan - the Kashkadarya region. The features of the modern demographic situation are also considered.
Keywords: demography; regional economy; region; industry